Modeling Energy and Non-energy Substitution – A Survey of Elasticities - Manuel Frondel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Estimating the degree of substitution between energy and non-energy inputs is key for any evaluation of environmental and energy policies. Yet, given the large variety of substitution elasticities, the central question arises as to which measure would be most appropriate. Apparently, ALLEN's elasticities of substitution have been the most-used measures in applied production analysis. In line with Frondel (2004), this paper argues that cross-price elasticities are preferable for many practical purposes. This conclusion is based on a survey of classical substitution measures, such as those from ALLEN, MORISHIMA, and MCFADDEN. The survey also highlights the fact that cross-price elasticities are their essential ingredients. – – Die Kenntnis des Grads, mit dem der Produktionsfaktor Energie durch andere Inputs substituiert werden kann, ist eine wesentliche Voraussetzung für die Evaluierung von umwelt- und energiepolitischer Maßnahmen. Angesichts der großen Vielfalt an Substitutionsmaßen stellt sich die Frage, welches dafür am Besten geeignet ist. Während Allens Substitutionselastizitäten am häufigsten verwendet werden, wird in diesem Papier argumentiert, dass Kreuzpreiselastizitäten für viele praktische Zwecke zu bevorzugen sind. Diese Schlussfolgerung basiert auf einem theoretischen Überblick über die klassischen Substitutionsmaße, wie die von Allen, Morishima oder McFadden. Der Überblick betont die Tatsache, dass Kreuzpreiselastizitäten die wesentlichen Bestandteile all dieser Substitutionsmaße sind.
Keywords: C3; D2; 330; Cross-price elasticities; Allen partial elasticities; Morishima elasticities; Energiesubstitution; Substitutionselastizität; Theorie